2019
DOI: 10.1136/archdischild-2019-esdppp.118
|View full text |Cite
|
Sign up to set email alerts
|

P80 Objective pharmacodynamic evaluation of doxapram in preterm infants

Abstract: BackgroundPharmacodynamic evaluation is challenging in neonatal clinical care, and often based on subjective human interpretation of clinical signs and the available ‘snapshot’ of physiological parameters. High frequency data (≥ 1Hz) of bedside patient monitors provide the opportunity of continuous and objective drug evaluation.1 This study investigates the predictive value of continuously available vital and ventilatory parameters to evaluate doxapram therapy. Doxapram is a respiratory stimulant to avoid mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Two retrospective studies concluded that doxapram therapy may avoid mechanical ventilation (Prins et al, 2013;Flint et al, 2017a). In our earlier studies, doxapram therapy had a positive effect on the SpO 2 , the applied FiO 2 (Flint et al, 2017b), the oxygen need (SpO 2 /FiO 2 ratio), and hypoxia (cumulative oxygen shortage under the 89% limit) (Poppe et al, 2019). The present study is the first in which doxapram therapy effects were continuously evaluated in individual patients.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Two retrospective studies concluded that doxapram therapy may avoid mechanical ventilation (Prins et al, 2013;Flint et al, 2017a). In our earlier studies, doxapram therapy had a positive effect on the SpO 2 , the applied FiO 2 (Flint et al, 2017b), the oxygen need (SpO 2 /FiO 2 ratio), and hypoxia (cumulative oxygen shortage under the 89% limit) (Poppe et al, 2019). The present study is the first in which doxapram therapy effects were continuously evaluated in individual patients.…”
Section: Discussionmentioning
confidence: 55%
“…The first response to doxapram therapy can already inform the clinician on therapy outcome. Previously we have found that the SpO 2 /FiO 2 ratio in the 48 h around start of doxapram, corrected for postnatal age and mechanical ventilation before therapy start, was a predictor for therapy failure or success (Poppe et al, 2019). Clearance, and the related exposure and effect, may differ from the general preterm population in, for instance, those small for gestational age with different severity of illness and co-medication (Allegaert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations